2017
DOI: 10.1002/hrm.21844
|View full text |Cite
|
Sign up to set email alerts
|

Conditional altruism: Effects of HRM practices on the willingness of host‐country nationals to help expatriates

Abstract: The assistance of host-country nationals (HCNs) both within the workplace and in the external environment plays a significant role in expatriate adjustment and work performance on international assignments. Extant research exploring antecedents of HCNs' attitudes and behaviors toward expatriates focuses on personal and intrapersonal factors but overlooks organizational contextual effects. In this study, we propose and test a model that HCNs' willingness to help expatriates is influenced by HRM practices in int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 73 publications
(124 reference statements)
0
26
0
Order By: Relevance
“…Alfes, Truss, Soane, Rees, and Gatenby (2013); Barber, Huselid, and Becker (1999); Boon and Kalshoven (2014); Bulter and Teagarden (1993); Foss, Pedersen, Reinholt Fosgaard, and Stea (2015); Hoque, Wass, Bacon, and Jones (2018); Kilroy, Flood, Bosak, and Chênevert (2017); McCowan, Bowen, Huselid, and Becker (1999); Messersmith, Kim, and Patel (2018); Neves, Almeida, and Velez (2018); Sanders and Yang (2016); Shen, Kang, and Dowling (2018)…”
Section: Shrm Research In Hrm and Hrmj: What Has Been Published And Wmentioning
confidence: 99%
“…Alfes, Truss, Soane, Rees, and Gatenby (2013); Barber, Huselid, and Becker (1999); Boon and Kalshoven (2014); Bulter and Teagarden (1993); Foss, Pedersen, Reinholt Fosgaard, and Stea (2015); Hoque, Wass, Bacon, and Jones (2018); Kilroy, Flood, Bosak, and Chênevert (2017); McCowan, Bowen, Huselid, and Becker (1999); Messersmith, Kim, and Patel (2018); Neves, Almeida, and Velez (2018); Sanders and Yang (2016); Shen, Kang, and Dowling (2018)…”
Section: Shrm Research In Hrm and Hrmj: What Has Been Published And Wmentioning
confidence: 99%
“…Trust plays a critical role in social exchange for the fact that when one person provides a benefit to another, he or she must trust that the other person will reciprocate (DeConinck, 2010). In the process of organizational social exchange, in case an employee believes that others are benevolent, and have integrity and ability, this employee has a propensity to support and believe in others (Shen et al , 2018; Yoon et al , 2016).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In addition, earlier scholarly work has also taken factors that are related to one’s individual characteristics into account, such as self-efficacy and personality, and inter-personal factors like trust and lead-member exchange (Burmeister et al , 2018; Serenko et al , 2016; see for an exemplary review Wang and Noe, 2010). Some scholars have focused on the impact of socially responsible human resource management (hereafter SRHRM), and their research has shown that companies conducting HRM practices in socially responsible ways have enhanced the well-being of their employees (Shen and Benson, 2016; Shen et al , 2018). According to the corporate social responsibility (CSR) literature, SRHRM can foster organizational trust and identification (Farooq et al , 2017; Shen and Benson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, social identity theory is appropriate here to explain how responsible leadership and SRHRM affects employee outcomes. Additionally, social exchange theory posits that individuals' voluntary actions are motivated by the returns they expect from others (Blau, 1964), explaining the social and psychological process underlying the relationship between employees and their organizations (Shen et al, 2018). Based on the norm of reciprocity, it suggests that the investments and inducements that organizations provide for employees through HR practices inspire employees to reciprocate by engaging in extra-role work behaviors that directly benefit the organization (Gould-Williams, 2007).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%